The Question of Value Neutrality in Science - Paitlová, Jitka (Teorie vědy / Theory of Science, 2014)
This study deals with the analysis of the question of "Value Neutrality" (Wertfreiheit) in science and proposed solution held by critical rationalist Hans Albert. First of all, Albert rejects two contrasting positions: ignorance of value judgments by logical positivists and the existentialist adoration on the other hand. On the contrary, through the so-called "bridging principles" he seeks to bridge the gap between knowledge on the one hand and the decision (i.e., evaluation) on the other. Following Max Weber he recognizes the principle of value neutrality in science, but only in the area of object-oriented language, for science as a technological system of statements is only informative, not normative. This does not preclude assessment on the level of objects (mainly social sciences) and the level of the value base (all sciences). In addition, this study addresses the issue of the value of science itself, and finally a brief introduction to the concept of critical rationalism that Albert proposed as a possible "way of life" (Lebensweise).